Between “the Most Holy Trinity” and the “people of Éire”: Nationalist Metanarrativity and Constitutional Identity - McCarthy, Peter (Trinity College Dublin. School of Law. Discipline of Law, 2026)
In this thesis I argue that Bunreacht na hÉireann maintains at its normative core a conception of Ireland which preserves an element of ethno-symbolic nationalism. I base this argument in analysis of the text and the attendant context of its interpreters, in particular, the metanarrativity contained in the Preamble. That the emphasis on this aspect of the text has significantly diminished over the nearly ninety-year history of the Constitution, I suggest, demonstrates that the judicial interpretive community have developed a postmodern scepticism in relation to the Gaelic Catholic nationalism which remains therein. I suggest that this scepticism emanates necessarily from the ambivalence and indeterminacy in the Constitution's theory of legitimacy; that it is couched in an overtly theistic natural law foundation, while textual and social developments have gone in the direction of greater secularity and liberal nationalism. I interrogate this developmental process from an initial syncretism between Between “the Most Holy Trinity” and the “people of Éire” to the current moment in which the procedural popular sovereignty of the Irish citizenry is theoretically unconstrained by the natural law foundations from which it is justified. Furthermore, I argue that we can situate the introduction -and heretofore minimal utilisation- of the `constitutional identity' doctrine within Irish jurisprudence as demonstrative of a reluctance by a majority of the Supreme Courts to engage in a modality of judicial reasoning which in the Irish context is inextricably linked to a metanarrativity of national identity.
APPROVED
Keywords: Constitutional Law; Constitutional History; Constitutional Identity